Influence of heat transfer dynamics on hardness distribution after quenching - Liščić, Božidar (Kovine zlitine tehnologije, 1997)
The pattern of hardness distribution on round bars' cross-section after quenching was studied in relation to the change of heat transfer on the workpiece surface. It was found that a 'delayer quenching', producing a discontinuous change of cooling rate, may result in higher hardness in the core, than aat the surface. This phenomenon called 'inverse hardening' has been theoretically explained by Shimizu and Tamura. It depends on: hardenability of the steel, cross-section size of the workpiece and on quenching condition, and is related to the incubation period consumed before the cooling rate was changed. Own experiments using cylindrical specimens of 50 mm Dia, made of AISI-4140 steel, have shown that Controllable Delayed Quenching (CQD) technology has a great potential to increase the depth of hardening, compared to conventional quenching practice. Bending fatigue tests with inverse hardened and tempered specimens have shown a significant increase of the fatigue life compared to specimens having normal haardness distribution after quenching. CDQ-technology and 'inverse haardening' can reproducibly be realized using adequate steel hardenability and cross-section size of the workpiece, by quenching in PAG polymer-solution of high concentrtion, or in high pressure-circulated gasses.
Keywords: jekla; trdota; kaljenje; prenos toplote